Effect of Papaya ringspot virus watermelon strain on growth, yield and quality of melon - Dewa Gede Wiryangga Selangga; I Gede Rai Maya Temaja; Gusti Ngurah Alit Susanta Wirya; I Putu Sudiarta; Listihani Listihani; Wafa’ Nur Hanifah; Restiana Maulinda (Universitas Lampung, 2026)
Papaya ringspot virus watermelon strain (PRSV-W) is a member of the genus Potyvirus that infects Cucurbitaceae crops. The first occurrence of PRSV-W in Indonesia was reported in Bali in 2022. However, information regarding yield loss caused by PRSV-W infection in melon has not yet been reported. This study aimed to analyze yield loss and changes in fruit quality of melon resulting from PRSV-W infection. The research methods included individual and population level disease observations, assessment of agronomic variables and disease severity, yield loss estimation, and data analysis. Observations were conducted at the Pegok Experimental Farm, Faculty of Agriculture, Udayana University, covering an area of 1000 m². The observed plant ages ranged from 6 to 66 days after planting (dap). Mosaic disease development was observed from 18 dap until before harvest. The highest disease incidence and disease severity recorded at the end of the observation period were 58.4% and 61.8%, respectively. Actual yield loss, calculated by comparing mosaic symptomatic and asymptomatic melon plants, reached 49.45%. The most prominent quality defects were changes in fruit color and shape and fruit malformation, with values of 14.06% and 17.5%, respectively. The greatest economic loss occurred in plots with an AUDPC value of 751, resulting in a total yield loss of IDR 15,721,500. Yield loss showed strong correlations with disease incidence and disease severity, with correlation values of 95.41% and 96.19%, respectively. PRSV-W infection altered fruit skin color from yellow-orange to pale yellow with ringspot symptoms, and PRSV-W was detected in the skin tissues of infected fruits. In addition, PRSV-W infection reduced fruit sweetness to 9–12 °Brix, whereas healthy fruits exhibited sweetness levels of 14–17 °Brix.